Themes in community resilience: A meta-synthesis of 16 years of Idaho Community Reviews. Issue 1 (1st January 2018) - Hightree, Joshua; Kliskey, Andrew; Higgins, Lorie; Alessa, Lilian; Laninga, Tammi; Barrett, Jon
Abstract: To address socioeconomic challenges in rural Idaho, some communities have participated in a community review process through Idaho Rural Partnership's Community Review program. To understand patterns and trends in perceptions of local assets and challenges, we used a mixed-methods approach, including aggregation and statistical analysis of survey data collected over the course of 15 years, and qualitative analysis of open-ended survey questions, focus group data, and assessment reports. Respondents were most dissatisfied with employment and availability of higher education, and most satisfied with items indicative of strengths in bonding social and cultural capital. Satisfaction for some community characteristics was found to vary by time, remoteness, and population size. Results aligned well with other research on rural wellbeing. Findings can help direct community planners and residents addressing local issues to develop response strategies, such as increased focus on infrastructure, health, community branding and placemaking, and building local leadership capacity.